Lead Isotope Ratio Optimization using Q-ICP-MS for Volcanic Rocks - Mutiara Effendi; Indah Yuni Prasetiawati; Melnawati Rohman (Jurnal Kimia Sains dan Aplikasi, 2025)
Lead isotope ratios are a valuable tool for tracing the origin and evolution of volcanic rocks, supporting exploration of critical metals for renewable energy. While multi-collector and thermal ionization mass spectrometers offer superior precision, they are costly and time-consuming. For rapid, preliminary analyses of lead-rich samples, quadrupole mass spectrometry can provide sufficient results with appropriate optimization. This study aims to optimize the measurement of lead isotope ratios using quadrupole ICP-MS (Q-ICP-MS) for several volcanic rocks from Indonesia. After multivariate optimization of the main operating conditions (dwell time 1-3 ms, sweep number 2000-4000, and replicate 2-6), the isotopic ratios were measured with an internal precision of 0.05-0.9 %RSD; the accuracy is 99.97-103.79 %, and reproducibility is 8.8-10.5 Horwitz value. Our measurements agree well with the reported data of certified reference material AGV-2 and within analytical uncertainties.